Polydopamine Nanomaterials: Recent Advances in Synthesis Methods and Applications - Ball, Vincent (Frontiers in Bioengineering and Biotechnology, 2018)
Polydopamine (PDA) the final oxidation product of dopamine or other catecholamines, attracted much attention as versatile coatings allowing to cover the surface of almost all materials with a conformal layer of adjustable thickness from a few to about 100 nm. These PDA layers can subsequently be modified with molecules carrying nucleophilic groups or with metallic nanoparticles from solutions containing metallic cations. However, simultaneously to the PDA film deposition on surfaces, the reaction products obtained from the oxidation of catecholamines in solution are useless precipitates. Hence some recent effort has been devoted to produce PDA in the form of nanoparticles. It is the aim of this short review to give a comprehensive description of the synthesis methods yielding to PDA nanoparticles in the absence or in the presence of templating agents (polymers, polyelectrolytes, surfactants, proteins and even some small organic molecules). Finally some first applications of the obtained PDA nanoparticles will be described.